Directional modifying of inorganic oxides surface by catalytic active complexes of cobalt with 1,3-diazoles - Belyakova, L. A.; Linkov, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
In this study a technique for the surface modification of ceramic membranes, consisting of 70 % AI2O3 and 30% Zr02 by disperse silica and complexes of cobalt with 1.3-diazoles has been developed. This was done by first reacting them with silica and then with γ-aminopropyltriethoxysilane, cyanuric chloride (or 1,10-diiododecane) and 1.3-diazole (imidazole or histamine). Heterogenized cobalt complexes with 1,3-diazoles, grafted onto the membrane surfaces, were obtained. It was established that the cobalt complexes with 1,3-diazoles had a deformed tetrahedral structure and it was only the nitrogen atoms of the grafted heterocycles of imidazole which were involved in the formation of four co-ordinate metal complexes. The catalytic activity of the produced membranes in the reaction of the liquid phase oxidation of cumene by molecular oxygen under mild conditions (atmospheric pressure and a temperature less than 100 °C) has been demonstrated. A study of the oxidation mechanism revealed that the reaction proceeds via the formation of oxygenated complexes of 1,3-diazoles with cobalt ions on the catalytic membrane surface. The formation of radicals takes place due to the oxygenation of heterogenized cobalt complexes, according to the following reaction: O2∙Co(II) → O2 -Co(III). The catalytic reaction of cumene oxidation proceeds with the participation of Co(III)-catalysts according to a mechanism involving electron transfer. The newly developed method for the preparation of catalytic membranes can also be used for the manufacturing of selective ceramic membranes with hydrophobic or hydrophilic surfaces.